Digital-Visual Imagery In Marketing Communication of Modern Lifestyle: Analysis of Property Advertisement In - I Putu Dedy Wahyu Wijaya; Z. Hidayat (Syntax Corporation, 2022)
The use of Instagram as a marketing medium is currently a massive undertaking. Its progress creates various new cultures in today's society. Not a few people or institutions have changed their behavior to enjoy the benefit of Instagram's growing popularity. One agency that is also taking advantage of this upturn of Instagram is a property developer. They use Instagram as part of their 360 marketing methods. In line with this, Instagram is also used to signify activities and various forms of goods that are considered to have specific values. The advancement of technology also accelerates and facilitates the creation of a new culture in society. Agencies that have seen the opportunity to take advantage of this cultural and lifestyle reform, try to spread their ads through the same platform: Instagram, with correlating themes related to society's trend. Instagram, an image-based social media, pushed these developers to compete to design various kinds of illustrations to influence their target market. Based on those premises mentioned above, this research was carried out by analyzing Instagram posts from property developer accounts in 2020. The method used is semiotics by Charles Pierce. During the research, it was found that property developers' accounts often take advantage of a particular moment to boost their visual campaigns. These moments are often related to hobbies, lifestyle, places, and everyday items. Thus they can create a connection between them and their target consumers via Instagram's visual media.